Extractive industries: transforming states and improving economic management - Tony Addison; Alan Roe (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
While market mechanisms and private initiatives can deliver much for development, public action is also necessary to: maximize the economic benefits of the extractive industries; manage potentially large capital and revenues flows; minimize adverse environmental and social impacts; and steer the economy towards a net zero future. An 'All of Government Approach' is desirable: to coordinate action, especially between local and central government, around a longterm sector strategy; and to provide the private sector with a consistent policy framework which encourages investment. The paper also emphasizes improvements to public finance, including taxation, especially those tax issues relating to national strategies for net zero, as well as the politically challenging task of removing fossil fuel subsidies. The paper discusses the many decisions involved in the macroeconomic management of resource booms, including accumulating (or paying off) debt and how much to spend and how much to save in a sovereign wealth fund.
Keywords: L71; L72; O11; Q32; 330; extractive industries; oil; mining; natural gas; sovereign wealth funds; taxation